3D Printing of Interdigitated Li‐Ion Microbattery Architectures. (18th June 2013) - Sun, Ke; Wei, Teng‐Sing; Ahn, Bok Yeop; Seo, Jung Yoon; Dillon, Shen J.; Lewis, Jennifer A.
<x xml:space="preserve">Abstract</x> 3D interdigitated microbattery architectures (3D‐IMA) are fabricated by printing concentrated lithium oxide‐based inks. The microbatteries are composed of interdigitated, high‐aspect ratio cathode and anode structures. Our 3D‐IMA, which exhibit high areal energy and power densities, may find potential application in autonomously powered microdevices. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>